2019
DOI: 10.1038/s41598-019-48398-5
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of MgAC-Fe3O4/TiO2 hybrid nanocomposites via sol-gel chemistry for water treatment by photo-Fenton and photocatalytic reactions

Abstract: MgAC-Fe 3 O 4 /TiO 2 hybrid nanocomposites were synthesized in different ratios of MgAC-Fe 3 O 4 and TiO 2 precursor. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray fluorescence spectrometry (XRF), electron spin resonance spectrometry (ESR), Brunauer-Emmett-Teller (BET), photoluminescence (PL), and UV photoelectron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Li et al [ 47 ] indicated that the addition of graphene oxide to TiO 2 -Fe 3 O 4 materials improved their photocatalytic properties in Vis light. Bui et al [ 48 ] described the modification of TiO 2 -Fe 3 O 4 , with magnesium amino-functionalized clay via the sol-gel method. Additionally, the authors used the obtained materials for the water treatment process realized by applying photo-Fenton and photocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 47 ] indicated that the addition of graphene oxide to TiO 2 -Fe 3 O 4 materials improved their photocatalytic properties in Vis light. Bui et al [ 48 ] described the modification of TiO 2 -Fe 3 O 4 , with magnesium amino-functionalized clay via the sol-gel method. Additionally, the authors used the obtained materials for the water treatment process realized by applying photo-Fenton and photocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocatalyst has emerged as an alternative to increase catalytic efficiency, since it has advantages over commercial catalysts, such as higher specific surface area and porosity, making them with great potential application in heterogeneous photocatalysis 10 . One of the strategies used to increase the photocatalytic activity of nanocatalysts is the usage of hybridization with noble metal and metals, in order to reduce the recombination between photoelectrons/holes pairs and reducing the energy required to its photoactivation, allowing its application to visible radiation [11][12][13][14][15][16] . In addition, Rhodamine B dye (RhB) (C 28 H 31 N 2 O 3 Cl), a highly water soluble organic cation dye, belongings to the class of xanthenes, whose contact with humans can cause irritation to the skin, airways and eyes 17 .…”
mentioning
confidence: 99%
“…The combination of MgAC and other nanomaterials for environmental treatment purposes in the rst step showed positive responses in both adsorption performance, stability, and reusability. [19][20][21][22][23] In such cases, MgAC with amine functional groups, which acted as interaction sites with other nanomaterials, signicantly increased loading efficiency, a homogeneous dispersion, and created many individual active sites, avoiding agglomeration, and ensuring long-term structural stability. 24,25 In this work, a simple two-step electrochemical method using MgAC as a great stabilizer and reductant is introduced for the rst time, facilitating the better uniform formation and long-term stability of Ag@ZnO nanoparticles (NPs) on the MgAC matrix without using any chemical additives.…”
Section: Introductionmentioning
confidence: 99%